Peran Kader Bina Keluarga Balita Holistik Integratif (BKB HI) melalui Program Surveilan untuk Optimalisasi Pemantauan Kesehatan Ibu dan Anak - Mufidatun, Ikhtiarisca Olifia (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Maternal mortality ratio and infant mortality rate are still high in Indonesia. Bantul is one of the districts in D.I. Yogyakarta with the highest infant mortality rate. One of the public health interventions that has been undertaken to address this issue is maternal and child health surveillance program with the cadres in the implementation of the holistic integragrative toddler family building program (BKB HI) being the leading implementers. This study aimed to describe the role of cadres in the implementation of the holistic integragrative toddler family building program (BKB HI) in maternal and child health surveillance to optimize maternal and child health care services in Bantul District, D.I. Yogyakarta. This was a qualitative study using case study approach. It was conducted in Bantul, D.I.Yogyakarta. Key informants were selected by criterion sampling. The data were collected by in-depth interview, focus group discussion, observation, and document review. Data validity was checked by triangulation. Community based maternal and child health surveillance program has been long implemented. The tasks of these cadres in the implementation of the holistic integragrative toddler family building program (BKB HI) included advocacy and monitoring of maternal and child health in the areas of BKB. The implementation of these surveillance program had some obstacles, including low insentive of cadres or community health worker, inactive community health worker, lack of awareness among community members on maternal and child health issues. As the conclusion, community health workers or cadres help improve the quality of maternal and child health care by surveillance program, although their performances have yet to be enhanced.